Instant Drinks with Amaranth Flour: Simulation of Mechatronic Systems of Production - Popov Anatoly M.; Plotnikov Konstantin B.; Ivanov Pavel P.; Donya Denis V.; Pachkin Sergei G.; Plotnikova Irina O. (Техника и технология пищевых производств)
Introduction. The world market of instant drinks is a highly competitive environment. New mechatronic production systems can help food companies maintain their competitiveness: they determine process modes, analyze them, and choose the optimal parameters, thus increasing the efficiency of the whole food enterprise. Another problem is the low biological and nutrient value of the finished product. New biologically active instant drinks could solve the problem that occurs in conditions of unsocial hours and unbalanced diet. Products of plant origin contain a lot of useful substances. Amaranth flour increases the biological value of the final products. The research objective was to develop mechatronic systems that could be used to produce instant drinks fortified with amaranth flour at the granulation stage. Study objects and methods. The present research featured a new line of production of instant granular drinks fortified with amaranth flour. The study focused on the granulation section. A drum vibro-granulator with controlled segregated flows was used to make a hardware design of the granulation process. The granulation process often demonstrates an unstable particle size distribution, which is associated with non-uniform mixing of the dry bulk components with the binder solution. A mechatronic module can solve this problem. However, it requires detailed information about the process conditions. Results and discussion. The research determined the specific energy consumption on the operating and design parameters for the granulation process in the new drum vibro-granulator. The experiment made it possible to obtain the optimal process parameters and improve the quality of the finished product. The flow rate of the binder solution depended on the readings of the power consumed by the kneading body engine, which stabilized the system. The value of this parameter is so small that its direct regulation is technically impossible. The paper introduces a block diagram of a multi-circuit cascade system to control the quality of the mixture automatically. The authors installed a valve on the pipeline that feeds the binder fluid in the pressure tank. The valve made it possible to control the process with sufficient accuracy. Conclusion. In the new mechatronic module of the drum vibro-granulator, the quality indicators of the resulting mix depend on the amount of power consumed by the kneading body engine and on the level of the binder solution in the pressure vessel.